A Comparison between the comunicative aproach and grammar-based method used to teach children of 7mo básica B, and 7mo básica C at Bilingüe Interamericano school - Moscoso, Isabel
This thesis is about a comparative analysis between the Communicative Approach, and the Grammar-based method used in EFL classrooms. The purpose of the thesis is to find out which of the two methods works better in a group of students. The analysis has been made between two 7mos de Básica from the Bilingue Interamericano School. 7mo de Básica B, and 7mo de Básica C. Here you will also find Unit and lesson plans for each method according to the group of students chosen for the study. Each Unit and lesson plan has been carefully prepared in order to meet the needs of the students. The structure used for the comparative analysis is the Verb to be in the Simple Present with its Affirmative, Negative, Yes/No questions, and informational questions with Wh-words. Also there are tables and charts with their statistical graphs which show the results of each study. The results showed that the Communicative Approach was more encouraging to the students in the learning of English, as opposed to the Grammar-based method which was not as successful. This thesis can be of much help to English teachers because it deals with the basics of teaching using the best tools there are available in the world of English linguistics. Finally there are a series of conclusions and recommendations given to teachers who are interested in finding the best method to teach English